The Pol Pot regime : race, power, and genocide in Cambodia under the Khmer Rouge, 1975 - 79 - Kiernan, Ben 1953- (Yale Univ. Press, 1996)
The Khmer Rouge revolution turned Cambodia into grisly killing fields, as the Pol Pot regime murdered or starved to death a million and a half of Cambodia's eight million inhabitants. This book - the first comprehensive study of the Pol Pot regime - describes the violent origins, social context, and course of the revolution, providing a new answer to the question of why a group of Cambodian intellectuals imposed genocide on their own country.